1993
DOI: 10.1515/znc-1993-5-611
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Light-Harvesting Complexes from Chlorella fusca (Chlorophyceae) and Mantoniella squamata (Prasinophyceae)

Abstract: Reconstitution experiments of light-harvesting complexes were performed with the green alga Chlorella fusca and the chlorophyll c-containing prasinophyte Mantoniella squamata using a modified method according to Plumley and Schmidt [Proc. N atl. Acad. Sei. U .S.A . 84, 146 -150 (1987)]. Changing the pigment supply quantitatively or qualitatively in the reconsti­tution mixture homologous and heterologous reconstitutes were obtained. In contrast to higher plants, light-harvesting polypeptides from green algae ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Nonstoichiometric carotenoid contents could also be explained by the fact that a single pigment-protein species comprises several subpopulations with heterogeneous pigment composition. The higher lutein content found in r-LHCI-730 as compared with n-LHCI-730 may also be the result of variability in pigment binding such as has been reported previously for LHCII (42,43). Regardless of the reason of the nonstoichiometric carotenoid levels, the molar carotenoid͞Chl ratio of about 0.2 for LHCI-730 in the present study is in accordance with ratios calculated for different LHCIIs (44), although somewhat higher values have been obtained by others (41,45).…”
Section: Discussionmentioning
confidence: 51%
“…Nonstoichiometric carotenoid contents could also be explained by the fact that a single pigment-protein species comprises several subpopulations with heterogeneous pigment composition. The higher lutein content found in r-LHCI-730 as compared with n-LHCI-730 may also be the result of variability in pigment binding such as has been reported previously for LHCII (42,43). Regardless of the reason of the nonstoichiometric carotenoid levels, the molar carotenoid͞Chl ratio of about 0.2 for LHCI-730 in the present study is in accordance with ratios calculated for different LHCIIs (44), although somewhat higher values have been obtained by others (41,45).…”
Section: Discussionmentioning
confidence: 51%
“…This was proposed for Chl binding by LHCI in barley (60), and results obtained with maize seedlings exposed to intermittent light also revealed flexibility in pigment binding in vivo (61). Additionally, reconstitution studies demonstrated the interchangeability of LHC proteins and carotenoids from alga and higher plants (21,62,63).…”
Section: Resultsmentioning
confidence: 78%
“…We conclude that the cooperative effect is not due to zeaxanthin binding to PsbS. (50), which includes many members from higher plants, green algae, red algae, and chromophyta (36,51). These proteins, with antenna function, cooperatively bind chlorophyll and xanthophyll chromophores, which are both needed for the assembly of pigmentprotein complexes in vivo and in vitro (32).…”
Section: Figure 9 Conformational Analysis Of Recombinant Psbs Refoldmentioning
confidence: 99%